THE ROLE OF GASTRONOMY IN THE DEVELOPMENT OF TOURISM INDUSTRY - Sidiqxo’jayeva Adolat Ravshan qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Gastronomic tourism, an increasingly popular niche of the travel business, provides a unique combination of gastronomic pleasures and cultural exploration. This thesis studies how food influences tourist destination preferences, promotes cultural interchange, and contributes to sustainable tourism. The project investigates the economic, cultural, and environmental implications of gourmet tourism through case studies, surveys, and stakeholder interviews. It also identifies difficulties, such as the risk of over-commercialization and resource depletion, and proposes methods to encourage authentic and sustainable culinary tourism.